Kontestasi Dan Resepsi Akademis Atas Fatwa Mui Tentang Covid-19: Tinjauan Bibliografis Atas Monografi Tahun 2020-2021 - Fawaid, Ahmad (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2021)
Abstract: This study aims to observe the contestation and academic reception of fatwas issued by the Indonesian Ulema Council (MUI) regarding Covid-19. These fatwas invite many responses in academic circles written in reputable journal articles. With a qualitative research paradigm and using Hans Robert Jauss text reception theory, this research concludes that; this study found four typologies of the MUI Fatwa monograph on Covid-19 during 2020-2021; namely (1) Monograph Typology, which discusses the Role of Fatwa (6 titles); (2) Discussing aspects of contact with other scientific disciplines, such as Maqāṣid,; (3) Unraveling the 'tangled thread' conflicting interpretations of the fatwa; (4) an article that measures the level of obedience of the Indonesian Muslim community to the MUI fatwa. Of the existing articles, 13 were built with justification based on the text, 5 articles were built with apologetic reasoning, and 3 used critical reasoning. From this conclusion, this study confirms that the academic response to the MUI Fatwa on Covid-19 also experienced Fragmentation, Resistance, and Appreciation.